이소골에 장착된 전자기 플로팅매스 진동체에 대한 집중 질량-스프링 모델의 제안 - 성기웅; 김민우; 이장우; 임형규; 정의성; 김동욱; 이명원; 이정현; 김명남; 이규엽; 이상흔; 박일용; et al. (Journal of biomedical engineering research, 2009)
Implantable middle ear hearing devices (IMEHDs) have been widely studied as an alternative hearing aids to solve the problems of conventional hearing aids. Vibration transducer of middle ear hearing aids is a key component because vibration characteristics of transducer is directly involved performance of hearing aids. So, the study about middle ear hearing aids concentrate on the transducers. A floating mass type transducer is most efficient. In this paper, we suggest a lumped mechanical model of electromagnetic floating mass transducer implanted on human middle ear. The proposed model enables analysis of the vibration characteristics of a floating mass transducer and prediction of the variation after implant on ossicle that offers a simple and easy to analyze. The parameters was drawn based on the components and the structures of transducer. The Lumped mechanical model was converted by the electrical-mechanical equivalent model, and simulated using PSpice. So, we investigated vibration characteristics of transducer influenced it's components. And we predict vibration characteristics of stapes footplate due to implanted transducer's vibration using combining model of transducer and human ear. To prove the feasibility of the suggested model, we fabricated a differential floating mass transducer (DFMT) as one of floating mass transducers and performed experiments using the human temporal bones.